IMPROVING STUDENTS’ ABILITY IN WRITING PROCEDURE TEXT BY USING PICTURE TO THE SECOND YEAR CLASS F STUDENTS OF SMP N 13 PONTIANAK - Soanti, Novie; ., Regina; Bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: This research is aimed to finding the answers? problems in teaching procedure text using picture to the students through classroom action research and have been done in three cycles. In cycle I, students were difficult to write their ideas into English because there were some unfamiliar words in the text. In cycle I, they were better because they divided into some groups. They were be motivated and paid more attention to the teacher. In the cycle III, the students more interested to the material because they have been met with the words likes lettuce, tomato, cheese, carrot, cucumber, butter, and bread. The researcher taken the average research?s? result from student?s score in each cycle, with the score; Cycle I was 50.16, higher score is 80 and lower score is 30; cycle II is 62.82, higher score is 85 and lower score is 45; cycle III is 79.22, higher score is 90 and lower score is 65. The result showed that students? ability improved and better in each cycle after they were teaching using a picture in writing procedure text. Key words       : students? ability, writing, procedure text, picture Abstrak: Penelitian ini bertujuan untuk menjawab masalah dalam mengajar teks prosedur menggunakan gambar kepada siswa dengan menggunakan penelitian tindakan kelas dan selesai melalui tiga siklus. Pada siklus I siswa sulit untuk mengekpresikan ide mereka ke dalam bahasa inggris karena beberapa kata sulit yang terdapat dalam teks. Pada siklus II, mereka lebih baik karena dibagi menjadi kelompok. Mereka termotivasi dan memperhatikan penjelasan guru. Pada siklus III, siswa sangat tertarik pada materi yang disampaikan karena sering mereka dapatkan dalam kehidupan sehari-hari, seperti selada, tomat, keju, wortel, mentimun, mentega dan roti. Penulis mengambil hasil penelitian (nilai rata-rata) dari peningkatan siswa setiap siklusnya; siklus I adalah 50.16, nilai tertinggi 80 dan terendah 30; Siklus II adalah 62.82, nilai tertinggi 85 dan terendah 45; Siklus III adalah 79.22, nilai tertinggi 90 dan terendah 65. Hasil akhir penelitian menunjukkan bahwa kemampuan siswa meningkat dan menjadi baik disetiap siklusnya setelah mereka diajar menggunakan gambar dalam menulis teks procedur. Kata inti: kemampuan menulis, prosedur teks, gambar